Implementation of a community of inquiry in teaching English as a foreign language in secondary schools: A literature review - Suharno Suharno; Didi Suherdi; Wawan Gunawan (Journal of Education and Learning (EduLearn), 2023)
Garrison, Anderson, and Archer’s community of inquiry (CoI) pedagogical framework for online distance learning is receiving greater attention as the COVID-19 takes place. Primary research concerns the researcher with English as a second language (ESL) instruction and acquisition English as a foreign language (EFL). More specifically, the study looked at 27 EFL-related articles from 133 published between 2011 and 2021 in respected journals that used the framework to teach languages. This study focused on the theoretical and practical applications of the framework in the field of foreign language distance teaching and learning that incorporates the use of information and communication of technology (ICT). It was concluded from the study’s findings that implementing the framework in secondary schools had little impact. Research suggests that the framework can be used in teaching English as foreign language (TEFL) and it is associated with improved language proficiency. Teachers must adapt to the distant learning pedagogical framework and its supporting technology, according to this study. The paper also advocates for further research into how the framework may be applied in secondary school.